2014
DOI: 10.1242/dev.111005
|View full text |Cite
|
Sign up to set email alerts
|

An Org-1–Tup transcriptional cascade reveals different types of alary muscles connecting internal organs in Drosophila

Abstract: The T-box transcription factor Tbx1 and the LIM-homeodomain transcription factor Islet1 are key components in regulatory circuits that generate myogenic and cardiogenic lineage diversity in chordates. We show here that Org-1 and Tup, the Drosophila orthologs of Tbx1 and Islet1, are co-expressed and required for formation of the heart-associated alary muscles (AMs) in the abdomen. The same holds true for lineage-related muscles in the thorax that have not been described previously, which we name thoracic alary-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 53 publications
2
52
0
Order By: Relevance
“…The myogenic function of Drosophila collier was first reported for its role in the specification of a hemisegmentally repeated abdominal muscle subtype (Crozatier and Vincent, 1999), where it is regulated by and required in cooperation with nau/MyoD for DA3 muscle differentiation (Enriquez et al, 2012;Dubois et al, 2007). This domain is notably distinct from that of org-1/Tbx1 action (Schaub et al, 2012;Boukhatmi et al, 2014). Two COE homologs in vertebrates, Ebf2 and Ebf3, regulate Myf5 and MyoD expressions in the somitic and branchiomeric muscles of Xenopus (Green and Vetter, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The myogenic function of Drosophila collier was first reported for its role in the specification of a hemisegmentally repeated abdominal muscle subtype (Crozatier and Vincent, 1999), where it is regulated by and required in cooperation with nau/MyoD for DA3 muscle differentiation (Enriquez et al, 2012;Dubois et al, 2007). This domain is notably distinct from that of org-1/Tbx1 action (Schaub et al, 2012;Boukhatmi et al, 2014). Two COE homologs in vertebrates, Ebf2 and Ebf3, regulate Myf5 and MyoD expressions in the somitic and branchiomeric muscles of Xenopus (Green and Vetter, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In vertebrates, Tbx1 is involved in activating MRF genes in the pharyngeal mesoderm (Kelly et al, 2004). In Drosophila, the Tbx1 homologue, Org-1, activates muscle-specific transcription factors temporally downstream of nau in several somatic muscles (Schaub et al, 2012), and acts independently of nau in alary muscle development (Boukhatmi et al, 2014). collier (also known as knot), the Drosophila homolog and founding member of the COE (Collier/Olfactory-I/Early B-Cell Factor) family of transcription factors, cooperates with Nau to cause differentiation of a distinct subset of muscles from those that require Org-1 (Enriquez et al, 2012;Dubois et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We, along with our colleagues, have shown recently that org-1 and tailup control embryonic AM development and that Org-1 directly regulates tup expression by binding to a distinct enhancer element (tup-ADME) [29]. Staining of adult hearts with antibodies against Tup showed that, in addition to pericardial cells, the nuclei of the VLMs were positive for Tup ( Figure 3E).…”
Section: Resultsmentioning
confidence: 70%
“…We found that, apart from cardiomyocytes, tup-ADME-GFP activity was present in the VLMs ( Figure 3G). When the ability of tup-ADME to bind Org-1 is abolished by base pair changes introduced into the three identified Org-1-binding motifs [29], this leads to a nearly complete loss of tup-ADME-orgI-IIImut-GFP activity in the VLMs. Because the expression in the cardiomyocytes stayed robust ( Figure 3H, asterisks), this demonstrates VLM-specific, direct regulation of the tup-ADME enhancer element by Org-1.…”
Section: Resultsmentioning
confidence: 99%
“…2). In the embryo, Drosophila AMs run immediately anterior to segmental boundaries, with their dorsal projections extending on either side of the boundary and connecting two adjacent AMs with one another (Boukhatmi et al, 2014) (Fig. 1).…”
Section: Alary Musclesmentioning
confidence: 99%